Study of Risk Factors for Conegnital Heart Defect in a Tertiary Level Hospital - Poly, Ferdousi Hossain; Afroza, Syeda; Rahman, Hasanur; Hassan, Md Imran (Journal of Dhaka Medical College, 2018)
A congenital heart defect is a heart problem which is present at birth, caused by improper development of the heart during fetal development. In majority of cases there is no known reason for the heart to develop improperly. Some type of congenital heart defects are related to chromosomal abnormality(5-6%), some are to single gene defect(3-5%) or environmental factors(2%). In 85-90% of cases there is no identifiable cause and are generally considered to be caused by multifactorial inheritance. There are some maternal factors which have some role in cardiovascular malformations. These include high maternal age(above 30 years), maternal obesity, consanguinity among the parents, fever during pregnancy, gestational diabetes mellitus, smoking, alcohol consumption, ingestion of any teratogenic drug including homeopathy and herbal medicine. Objective of the study: To evaluate the risk factors associated with congenital heart disease. Methodology: A case control study was conducted at paediatric department of Sir Salimullah Medical College & Mitford Hospital following approval of the protocol from 1st January 2013 to 30th June 2014. Children fulfilling the inclusion criteria-(0-5 year old children of both sexes admitted in paediatric units of Mitford Hospital with any type of congenital heart disease confirmed by echocardiography) were considered as cases. A similar number of age and sex matched children admitted in Mitford Hospital without any cardiac defect were considered as controls. Data were collected by questionnaire. Results: The results show that majority of the cases are male. Maternal age (27.09 ± 4.63) and BMI (24.10 ± 2.28) both are significantly higher in cases than those of controls. Among the cases 31.8% mothers had consanguineous marriage (p=0.001) and 27.1% mothers had history of fever during pregnancy whereas it was present in 9.3% mothers of controls, the difference is significant statistically (p=0.001). Among the cases 34.6% mothers had history of gestational diabetes mellitus and only 18.9% controls had so and the difference is significant statistically (p=0.014). Conclusion: Relatively old age and more weight during pregnancy, consanguinity between parents, fever during pregnancy, history of gestational diabetes mellitus are the main risk factors of congenital heart defects in children J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 51-56